- STRATEGI PEMBELAJARAN DI TINGKAT SMA UNTUK SISWA DENGAN AUTISM SPECTRUM DISORDER (ASD) - Amelia Rizky Idhartono; Hidayati, Nurul; Alsyah Safarina Subekti; Margareta Vernanda Moi (Universitas PGRI Adi Buana Surabaya, 2024)
A child with Autism Spectrum Disorder (ASD) having neurological disorder in their brain and nerve, that causing disorder in the area of cognitive, emotion, social behavior, and communication. There are many problems and challenges faced by teachers in teaching students with ASD. That is why, it is needed accuracy in choosing learning strategy for special needs students, especially students with ASD. The partner of this community service program were the 50 teachers and parents of SLB Mutiara Hati Surabaya. The community service program were held online at May 11th 2024 from 1 PM until 5 PM. At the program, there are also 2 students of Pkh University PGRI Adi Buana involved.